Strategies and innovations to improve the performance of barge transport - Wiegmans, Bart W.; Konings, Rob (European Journal of Transport and Infrastructure Research, 2007)
The extended competitive forces model is a tool for analysing the barge transport market in Europe. This paper examines several sub-sectors in the barge transport market with the aim of identifying potentially successful innovations and strategies for improving competitiveness. Barge transport faces some tough challenges if it is to significantly enhance its competitive position.